2015
DOI: 10.1007/s00402-015-2352-1
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicplasty for the treatment of a large traumatic osteochondral femoral head lesion: a case report with 2 year follow-up and review of the literature

Abstract: Different joint-preserving techniques have been described for the treatment of traumatic osteochondral lesions of the femoral head especially in young active patients. Mosaicplasty with autologous transplantation of osteochondral cylinders is an established surgical technique in the knee. Little evidence, however, exists for the treatment of osteochondral lesions in the hip using this technique. Here, we report on the result of treatment of a traumatic 5 cm(2) osteochondral lesion of the femoral head in a youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…However, this procedure is technically demanding and invasive because of the temporary luxation of the femoral head. Similar outcomes are reported in a review of the literature by Anthonissen et al 7 . This article describes a technique for an arthroscopic autologous osteochondral transplantation with a graft from the ipsilateral knee to the femoral head.…”
supporting
confidence: 78%
“…However, this procedure is technically demanding and invasive because of the temporary luxation of the femoral head. Similar outcomes are reported in a review of the literature by Anthonissen et al 7 . This article describes a technique for an arthroscopic autologous osteochondral transplantation with a graft from the ipsilateral knee to the femoral head.…”
supporting
confidence: 78%
“…Gagala et al[ 17 ] reported OAT for femoral head AVN by surgical dislocation in 20 patients and stated that OAT was a successful treatment method at precollapse stage. Anthonissen et al[ 18 ] reported OAT for the treatment of a large defect (2x2.5 cm) due to trauma with good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfactory clinical and radiographic results have been reported with mosaicplasty [2, 4, 6, 8, 9] or osteochondral allograft transplantation procedures [3, 5], which were performed for osteochondral defects of the femoral head via surgical hip dislocation. Girard et al [4] reported the results of mosaicplasty through a trochanteric flap osteotomy with surgical hip dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…However, utilization of the same technique for the hip joint is limited and technically demanding. Patients with osteochondral defects in the hip joint generally undergo surgical hip dislocation with or without a trochanteric slide osteotomy for placement of the osteochondral plug [2, 4, 6, 8, 9]. …”
Section: Introductionmentioning
confidence: 99%